2011
DOI: 10.1139/t11-060
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory investigation of the dynamic properties of tailings

Abstract: The dynamic response of tailings from a gold mine located in western Quebec was evaluated using cyclic laboratory testing. These tailings are classified as nonplastic silt and sand. Specimens of the tailings were prepared as slurries, consolidated to vertical effective stresses of 100–400 kPa, and subjected to cyclic direct simple shear testing with cyclic stress ratio, CSR, values between 0.075 and 0.15. The shear modulus reduction of the tailings under cyclic loading was found to be fairly similar to that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 33 publications
0
19
0
3
Order By: Relevance
“…Additionally, Thevanayagam and Martin (2001) and Hyde et al (2007) showed that the pre-and post-liquefaction consolidation curves of loose silts are parallel to each other in the e-p' plane (i.e. James, 2009;James et al 2011). Other testing results also showed that low plasticity tailings from hard rock mines behave as sandy soils in many ways (e.g.…”
Section: Page 8 Of 40mentioning
confidence: 99%
“…Additionally, Thevanayagam and Martin (2001) and Hyde et al (2007) showed that the pre-and post-liquefaction consolidation curves of loose silts are parallel to each other in the e-p' plane (i.e. James, 2009;James et al 2011). Other testing results also showed that low plasticity tailings from hard rock mines behave as sandy soils in many ways (e.g.…”
Section: Page 8 Of 40mentioning
confidence: 99%
“…In some cases (especially in the early stages of a project), the UCS values can be used to estimate the required strength from eq. [7], by postulating that f ≅ 35°(as typically obtained on tailings from hard rock mines under low normal stresses; e.g., James et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tests under reductive conditions were carried out in 80 mL glass vials filled with 64 mL of artificial mine tailing containing MCNPs and sealed with Teflon-lined caps. Additionally, we have also performed adsorption isotherm measurements using different concentrations of Cu (2,4,6,8,10,15,20,50, 100 and 200 mg/L) and 9 mL of MCNPs. The amount of Cu 2+ adsorbed per unit mass of wet nanoparticles was calculated through the Equation 1:…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Actually, the delivery of hazardous contaminants to the ecosystem, especially heavy metals into the water streams is a great concern (EPA, 2012). Chemical characterization of mine tailings has found the presence of heavy metals such as Hg 2+ , As 5+ , Pb 2+ , Cu 2+ , Zn 2+ , Ag + , Ni 2+ , Mn 2+ , and others [4]. Due to the recognized toxicity of heavy metals, the exposure to these elements, even in trace concentrations, is considered to be harmful to living beings [5,6].…”
Section: Introductionmentioning
confidence: 99%